(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The idea outlined in Arnett and Bergman's "Facial keys to orthodontic diagnosis and treatment planning, Parts I and II" directly informed the development of this radiography tool. This method's uniqueness, like that of the "Face Keys" articles, is in its focus on soft tissue facial measuring. In this article, different soft tissue structure qualities that contribute to an aesthetically pleasant face and should be taken into account during orthodontic treatment are compared between the North Indian and Caucasian female populations. The purpose of the current study was to demonstrate how North Indaian and Caucasian populations had different norms for soft tissue structure. Materials and Methods 60 North Indian females between the ages of 18 and 28 years had lateral cephalograms taken at the Himachal Institute of Dental Sciences in Paonta Sahib. Nemoceph software was used to trace the soft tissue profile as well as associated osseous and dental structures. Then, the soft tissue structure attributes of Arnett and North Indian female population was compared. Results: When compared to Caucasian women, North Indian women have shorter upper and lower lips, pog-pogs, and menton. The posterior height is more in North Indian females as compared to Caucasian females .The values of the projections to TVL are less in North Indian female population as compared to Caucasian population Because the face skeleton and the soft tissue that covers it vary depending on the population of females, all patients cannot be treated according to the same set of standards.